A historical map of Varanasi - Gengnagel, Jörg (Südasien-Institut, 2001)
[Dt.:]Der Autor beschäftigt sich mit einer alten Karte, die Varanasi, der heiligen Stadt der Hindus am Ganges im heutigen indischen Bundesstaat Uttar Pradesh, darstellt. Sie zeigt das alte Varanasi und wurde vielfach zitiert. Die Karte ist in kleinere Teile zerlegt und digitalisiert. Dadurch können verschiedene Ausschnitte angezeigt werden. Zudem wird der historische Background erklärt und erläutert. - [Engl.:]This web-based interactive presentation of Sukula's Mirror of KÁÐÍ is the result of a complete reading of the extensive legends inscribed on the map. In order to make all details accessible the map has been cut into 72 slightly overlapping detailed views (K1 to K72, indicated at the upper left). In each of these 72 windows you can click on the objects and a popup will open with the respective symbol, the Sanskrit and Hindi inscriptions in Devanagari script, the transcription as well as a translation and further remarks about textual references etc. A navigation cross in the upper right allows direct access to the surrounding maps. The 751 text blocks on the map have been numbered (S1 to S751). Every entry is indexed in the "General Index" and linked to the maps. To the left of the entries the number of the map is given, to the right the object-number, linked directly to the popup. The entry "34 - AbhayadavinÁyaka - S605f" thus stands for the sixth (indicated by the letter f) entry in popup S605 on map K34. The search for a specific entry on the map is - especially in the case of larger text blocks - sometimes difficult. We have therefore indicated the first name and the number of the popups in the flags that appear while moving with the mouse over the map
Gesehen am 27.01.14
Mitarb.: Michaela Dimmers; Birgit Mayer-König
Keywords: Website; Geschichtskarte; Varanasi